Isolation of competent actinomycetes strains from soil planted with three species of mint irrigated with olive mill wastewater - Oumaima Beroigui; Lahsen El Ghadraoui; Faouzi Errachidi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This study aimed to investigate the potential of actinomycetes in mitigating the environmental impact of olive mill wastewaters (OMWW) on plant-soil system. The objectives were to investigate the impacts of varying doses of OMWW on soil microflora, and to analyze the enzymatic profile of a selected group of isolated actinomycetes. Method: A physico-chemical characterization of soil parameters and OMWW was conducted. Microbiological analysis of OMWW was carried out to determine the presence of total aerobic mesophilic flora (FMAT), yeasts, and molds. An interaction study between different doses of OMWW and three varieties of mint (Mentha aquatica, Mentha piperita, and Mentha pulegium) was conducted over a 120-day period. Results: Analysis revealed that OMWW contained high levels of organic matter and mineral salts, resulting in elevated chemical oxygen demand and salinity. Application of OMWW at a dose of 5 L/m² enhanced soil microflora, but this effect diminished beyond this dose, except for actinomycetes, which remained resilient even at 10L/m². Enzymatic profile analysis of isolated actinomycetes indicated that the most competent strains were present in plots irrigated with 5 L/m² and 10 L/m² of OMWW, in combination with Mentha piperita and Mentha pulegium cultivation. Conclusion: This study demonstrates the potential of actinomycetes in addressing to meet the challenges inflicted by OMWW. Optimizing OMWW dosage can positively influence soil microflora, where actinomycetes exhibiting remarkable resilience at higher doses. These results contribute to understanding the use of microorganisms for olive oil industry waste management, in order to offer practical solutions to mitigate OMWW environmental impact. Highlights